Mathematics Learning Activities and the Role of Parents in the Covid-19 Pandemic - Halistin, Halistin; Patih, Tandri; Fitriyanti, Hepi (International Journal of Transdisciplinary Knowledge, 2022)
This study aimed (1) to determine the students’ mathematics learning activities during the Covid-19 pandemic at Rarowatu Utara State Junior High School. (2) knowing the role of parents of students during the Covid-19 pandemic at SMP Negeri Rarowatu Utara. The research method used is descriptive qualitative. The results showed that: 1) students’ mathematical learning activities were carried out using the WhatsApp application of online learning. The highest students’ mathematics learning activities are in the Writing Activities with a percentage of 22.20%, and the lowest activity is the Emotional Activities, which is 16.39%. 2) The role of parents during the Covid-19 pandemic at SMP Negeri Rarowatu Utara is that the majority of parents act as teachers at home, providing facilities and a comfortable home environment. However, it has not been able to increase knowledge in mathematics subjects.